An investigation into the role of ATM protein in mitochondrial defects associated with cardiovascular pathology resulting from insulin resistance - Blignaut, Marguerite (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.